P097 SHORT AND LONG-TERM COMPLICATIONS FOLLOWING ROBOTIC-ASSISTED RETROMUSCULAR VENTRAL HERNIA REPAIR. (25th November 2021) - Nielsen, Kristian Als; Frederichsen, Mathias; Valsamidis, Alexandros; Harthimmer, Mads; Helligsø, Per; Nielsen, Michael
Abstract: Aim: Robotic-assisted ventral hernia repair (rVHR) has become an attractive alternative to current laparoscopic and open procedures. The present study aims to determine short-and long-term complications following rVHR Material and Methods: Patients undergoing rVHR from 01/01 2017 until 21/06 2020 were identified from the electronic medical record system. The medical case notes were reviewed and a telephone interview conducted to determine short and long-term complications. Patients with symptoms related to the repair were examined by a specialist in hernia surgery. US or CT scan was performed to determine the presence of absence of complications Results: 85 patients were included. Mean age was 57.8 years, 54 were males (63.5%). Mean ASA-score was 2.12 and BMI was 30.2 kg/m 2 . 11 patients (13%) had diabetes, 22 (26%) were active smokers, 37 (44%) had hypertension and 7 (8%) were taking anti-coagulants. The mean hernial defect was 16.1 cm 2 and the mesh size was 205.4 cm 2 . Mean length of stay was 0.5 days and the follow-up time was 94 weeks. Hematoma was encountered in 10 (11.8%) patients. 8 (9.4%) reported of seroma and 1 (1.2%) of a superficial wound infection complicated by skin necrosis. 5 patients (5.9%) reported of chronic pain. 2 patients (2.3%) developed recurrence. Conclusions: The study demonstrates that rVHR is feasible and associated with few complications and a very low recurrence rate. Patients who had pain before surgery were likely to have less pain following the procedure. Due to the short hospital stay the procedure is suitable as an outpatient procedure.